2019
DOI: 10.3390/nano9091295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antimicrobial Activity of Magnesium-Doped Hydroxyapatite Suspensions

Abstract: Obtaining nanoscale materials has allowed for the miniaturization of components, which has led to the possibility of achieving more efficient devices with faster functions and much lower costs. While hydroxyapatite [HAp, Ca10(PO4)6(OH)2] is considered the most widely used material for medical applications in orthopedics, dentistry, and general surgery, the magnesium (Mg) is viewed as a promising biodegradable and biocompatible implant material. Furthermore, Mg is regarded as a strong candidate for developing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 71 publications
9
64
2
Order By: Relevance
“…The results obtained in this study are in accord with previously reported studies regarding the potential antimicrobial properties of materials and composite layers based on hydroxyapatite enhanced with various antimicrobial agents, such as metal ions, that are known to possess antimicrobial properties [36][37][38]. Despite the progress made in the biomedical filed, several studies have reported that the development of implant-related infection is still of great concern and that C. albicans can easily colonize and aggregate on prostheses and implants [39][40][41].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained in this study are in accord with previously reported studies regarding the potential antimicrobial properties of materials and composite layers based on hydroxyapatite enhanced with various antimicrobial agents, such as metal ions, that are known to possess antimicrobial properties [36][37][38]. Despite the progress made in the biomedical filed, several studies have reported that the development of implant-related infection is still of great concern and that C. albicans can easily colonize and aggregate on prostheses and implants [39][40][41].…”
Section: Resultssupporting
confidence: 90%
“…Thus, by placing in an ultrasonic bath the final gel for 12 h, its stability increased. The results presented in this study were sustained by previously reported studies [36][37][38], which state that hydroxyapatite could be enriched with various metal ions in order to exhibit antimicrobial properties. Nonetheless, this study emphasizes for the first time the obtaining of stable AgHAp solutions with antimicrobial properties, using an adapted synthesis method, for the development of new and improved coatings on the basis of silver-doped hydroxyapatite.…”
Section: Resultssupporting
confidence: 81%
“…The antimicrobial properties of thyme EO have been previously reported against a pathogenic and/or spoilage food-related bacterium [26,27], as well as against common bacterial strains, such as Staphylococcus aureus and Listeria monocytogenes [23]. Nonetheless, there are several emerging cations with both antimicrobial properties and important roles in the enhancement of the biological interactions of HAp with the surrounding tissues, amid which Mg 2+ comes into prominence [28][29][30]. Magnesium is one of the most important essential trace elements, being involved in the development of bones and connective tissues and possessing osteogenic and angiogenic stimulating properties, demonstrated both in vitro and in vivo [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [30], the authors explored the stability of Mg-doped HAp (Ca 10-x Mg x (PO 4 ) 6 (OH) 2 , x Mg = 0.1) suspensions, which were characterized by remarkable biocompatibility and antimicrobial efficacy against Pseudomonas aeruginosa, S. aureus, and Candida albicans microbial strains. The coupling of Mg doping and thyme EO antibacterial agents within a nano-HAp milieu might yield improved biofunctional properties.…”
Section: Introductionmentioning
confidence: 99%
“…A better osseointegration process in endosseous implants treated with photobiomodulation and ozone therapy has been described [26]. Modifications have been proposed to improve their integration but also to confer anti-infective properties [27][28][29]. Ozone-ultraviolet treatment of orthopedic titanium implants improved bone-implant osseointegration.…”
Section: Introductionmentioning
confidence: 99%